2020
DOI: 10.1177/1369433220939208
|View full text |Cite
|
Sign up to set email alerts
|

Shear behavior of large stud shear connectors embedded in ultra-high-performance concrete

Abstract: In this article, the static shear behavior of large-headed studs embedded in ultra-high-performance concrete was investigated by push-out test and numerical analysis. A total of nine push-out specimens with single and grouped studs embedded in ultra-high-performance concrete and normal strength concrete slabs were tested. In the testing process, only shank failure appeared without cracks occurring on the surface of ultra-high-performance concrete slab when the steel–ultra-high-performance concrete spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Data for the ultimate slip were collected from 194 pushout tests [1,15,16,20,22,23,25,28,69,78,[80][81][82][83][84]87,[90][91][92][93][97][98][99][105][106][107][108][109][110]. The target feature was the ultimate slip value (S u ) of the shear connection.…”
Section: Dataset For Slip Predictionmentioning
confidence: 99%
“…Data for the ultimate slip were collected from 194 pushout tests [1,15,16,20,22,23,25,28,69,78,[80][81][82][83][84]87,[90][91][92][93][97][98][99][105][106][107][108][109][110]. The target feature was the ultimate slip value (S u ) of the shear connection.…”
Section: Dataset For Slip Predictionmentioning
confidence: 99%
“…Unlike NSC stud connectors, studs embedded in high-strength concrete (HSC) are subject to higher local support strength, resulting in stud connectors failing with much more shearing than bending, so the former empirical formulae are no longer appropriate for the HSC situation. Kim et al [ 19 ], Cao et al [ 20 ], Kruszewski et al [ 21 ], and Hu et al [ 22 ] conducted an experimental study on headed studs in ultra-high performance concrete (UHPC). It was found that the high compressive strength and ultra-ductile properties of UHPC can provide adequate support and wrapping to the studs, causing the failure mode to pure shearing and UHPC to remain intact, significantly different from the connectors in NSC.…”
Section: Introductionmentioning
confidence: 99%
“…Shear stud connectors are widely used as shear connectors in steel-concrete composite bridges due to the advantage of direction independence, better ductility, and installation convenience (Li et al, 2021(Li et al, , 2022Lin et al, 2021;Hu et al, 2020). In order to resist relative sliding and restrict separation between steel beam and concrete plate, shear stud connectors are designed to support combined shear and tension loading, and in some fields of application, the tension force are non-negligible, for instance, anchorage system of cable-stayed composite bridge, negative moment section of simple supporting composite beams and steel-concrete joint section of hybrid girder bridges.…”
Section: Introductionmentioning
confidence: 99%